Resistant ovary syndrome: Pathogenesis and management strategies - Mu, Zhenni; Shen, Sinan; Lei, Lei (Frontiers in Medicine, 2022)
Resistant ovary syndrome (ROS) is a rare and difficult gynecological endocrine disorder that poses a serious risk to women's reproductive health. The clinical features are normal sex characteristics, regular female karyotype, and usual ovarian reserve, but elevated endogenous gonadotropin levels and low estrogen levels with primary or secondary amenorrhoea. Although there have been many case reports of the disease over the past 50 years, the pathogenesis of the disease is still poorly understood， and there are still no effective clinical management strategies. In this review, we have collected all the current reports on ROS and summarised the pathogenesis and treatment strategies for this disease, intending to provide some clinical references for the management and treatment of this group of patients and provide the foothold for future studies.